Выражение: 6+4а-5а+а-7а 5(n-2)-6(n+3)-3(2n-9) 5/7(2,8c- 4 целых 1/5)-2,4(5/6с-1,5d)

homya4okm homya4okm    2   23.09.2019 06:03    0

Ответы
Cornelia1313 Cornelia1313  08.10.2020 11:35
6+4а-5а+а-7а=6-7а

5(n-2)-6(n+3)-3(2n-9)=5n-10-6n-18-6n+27=9-7n

5/7(2,8c- 4 1/5)-2,4(5/6с-1,5d)=2c-3-2c+3,6d=3,6d-3
ПОКАЗАТЬ ОТВЕТЫ
Золушка251 Золушка251  08.10.2020 11:35
6+4а-5а+а-7а=6-7а
5(n-2)-6(n+3)-3(2n-9)=5n-10-6n-18-6n
+27=-7n-1
5/7(2,8c-4 1/5)-2,4(5/6c-1,5d)=2c-3 -2c+3,6d=3,6d-3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика